An innovative ethosuximide granule formulation designed for pediatric use: Comparative pharmacokinetics, safety, tolerability, and palatability profile versus reference syrup. Issue 1 (20th December 2022) - Diezi, Léonore; Dao, Kim; Jullien, Vincent; Roussel‐Maupetit, Caroline; Burton, Ingrid; André, Pascal; Bardinet, Carine; Rothuizen, Laura E.; Chtioui, Haithem; Manso‐Silvan, Maria A.; Guittet, Catherine; Brunner‐Ferber, Françoise; et al.
Abstract: Ethosuximide, the first‐line therapy for childhood absence epilepsy, is currently formulated as a syrup (Zarontin®, Pfizer) with a bitter taste and high sugar content, poorly adapted to children, and a ketogenic diet. The collaborative European FP7 project KIEKIDS aimed at developing an innovative sugar‐free, tasteless formulation convenient for pediatric use. This dual Phase‐I study evaluated two granule formulations based on lipid multiparticulate (LMP) technology. Two panels of 6 healthy adult volunteers underwent a randomized, placebo‐controlled, partly blinded, 3‐way cross‐over trial, comparing ethosuximide granules A or B with placebo granules and syrup at single 10 mg/kg doses. Corresponding plasma pharmacokinetic profiles of ethosuximide were compared, along with palatability, safety, and tolerability. The LMP granule A proved suboptimal due to bitterness and adherence to beaker walls, while the optimized granule B revealed excellent palatability, similar to placebo granules, and low adherence to glass. The relative bioavailability of granules A versus syrup, based on dose‐normalized C max and AUC0–∞ was 93.7% [90% CI: 76.3–115.1] and 96.1% [91.0–101.5], respectively. For granules B it was 87.6% [81.6–94.0] and 92.5% [88.5–96.6], respectively, with slightly delayed t max of 0.75 h [0.5–4.05] compared to syrup 0.5 h [0.3–0.8]. Tolerability visual analog scales revealed a trend for statistically non‐significant improvement versus syrup at peak (30 min) for transient dizziness (both granules), fatigue (granules A), and anxiety (granules B). The innovative ethosuximide granule formulation B achieves a suitable profile for pediatric use, being sugar‐free, tasteless, bioequivalent, and well‐tolerated while enabling precise adjustment to body weight. Abstract : Time profile of plasma ethosuximide concentrations according to formulation.